Ways of increasing the investment activity of the region enterprises - Abylkassimova, Zh.A.; Alibayeva, М.М.; Ramashova, A.N.; Gudalin , A.V. (BUKETOV BUSINESS REVIEW, 2019)
Effective development of the regional economy is impossible without an increase in investment activity. In the article the main directions of increasing the investment activity of enterprises in the region are noted, namely: fuller use of available raw materials with the provision of their integrated processing, modernization of the main industries of the region’s specialization with a focus on high-tech and competitive products with a high degree of readiness, introduction of innovative industries and technologies. However today the economy of enterprises in the region is faced with the problem of reducing investments in the real sector, most enterprises do not have enough own funds to purchase new equipment, develop an innovative product, develop an innovative business and diversify production. In order to fully realize the production potential of enterprises in the region, it is necessary to stimulate investment demand and increase investment activity, and to do this, use effective forms and methods to influence the behavior of investment subjects. The authors note that in order for the economic development of the regions of our country to go at an increasing rate, business entities must have an effective investment strategy, after all, it is investment that ultimately determines economic growth and the state of the economy of regional enterprises.